Mosquito vector diversity and abundance in southern Botswana, in a global context of emerging pathogen transmission - Ntebaleng Makate; Pleasure Ramatlho; Tefo Kesaobaka Kgoroebutswe; Katherine Laycock; Giacomo Maria Paganotti (AOSIS, 2022)
Background. The continued spread of infectious diseases by mosquitoes remains a formidable obstacle to the well-being of the people all over the world. Arboviruses are spread from one vertebrate host to another by vectors through intricate transmission cycles that involve the virus, the vertebrate host, and the vector. It is essential to acquire a better understanding of the current abundance and distribution of major vectors in order to adequately prepare for the possibility of arbovirus outbreaks. This is because the abundance and distribution of these major vectors determines the human populations that are at risk for the diseases that they transmit. The effects of climate change on the amount of mosquitoes and their ability to survive the seasons have had a substantial impact on the spread of diseases that are transmitted by vectors in many different parts of Botswana. Methods. The purpose was to collect mosquito samples in Gaborone and the neighboring areas in southern Botswana, including border stations. We collected different stages of the mosquito from each place, raised them to maturity, and then identified them. Both morphological and genetic studies were utilized in order to successfully identify the organism. The species of Culex mosquitoes accounted for 88.3% of the 5177 mosquitoes that were collected and identified, whereas the species of Aedes aegypti and Anopheles mosquitoes accounted for 11.5% and 0.2% respectively. Conclusions. These findings give entomological baseline data that will aid in the study of vectorial patterns and the estimation of future arboviral hazards provided by mosquitoes. Additionally, these findings document the diversity and abundance of mosquito species.